Voter Buying: Shaping the Electorate through Clientelism. Issue 2 (6th August 2015) - Hidalgo, F. Daniel; Nichter, Simeon
Abstract : Studies of clientelism typically assume that political machines distribute rewards to persuade or mobilize the existing electorate. We argue that rewards not only influence actions of the electorate, but can also shape its composition . Across the world, machines employ "voter buying" to import outsiders into their districts. Voter buying demonstrates how clientelism can underpin electoral fraud, and it offers an explanation of why machines deliver rewards when they cannot monitor vote choices. Our analyses suggest that voter buying dramatically influences municipal elections in Brazil. A regression discontinuity design suggests that voter audits—which undermined voter buying—decreased the electorate by 12 percentage points and reduced the likelihood of mayoral reelection by 18 percentage points. Consistent with voter buying, these effects are significantly greater in municipalities with large voter inflows, and where neighboring municipalities had large voter outflows. Findings are robust to an alternative research design using a different data set.